2014
DOI: 10.1111/fare.12058
|View full text |Cite
|
Sign up to set email alerts
|

Consistent and Inconsistent Contraception Among Young Women: Insights from Qualitative Interviews

Abstract: Qualitative interviews with young women attending community colleges were used to address why women who do not desire pregnancy vary in how consistently they use contraception. Based on our analysis of the women's sexual histories, we argue that five factors are key to promoting or discouraging consistent use of contraception: efficacy (women's ability to put an intention to contracept into practice), the actions and attitudes of male partners, being in a long‐term relationship, whether women experience side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Women often cite adverse side effects of hormonal methods and dislike of condoms (Horner et al, 2009;Reed, England, Littlejohn, Bass, & Caudillo, 2014;Whittaker et al, 2010), as well as convenience when condoms are not available or sexual encounters are unexpected, and diminished sexual pleasure while using condoms (Daley, 2014;Fennell, 2014;Higgins et al, 2014;Jones et al, 2009;Whittaker et al, 2010). Previous research has also highlighted the important influence of relationship context on the decision to use withdrawal (Brown et al, 2011;Whittaker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Women often cite adverse side effects of hormonal methods and dislike of condoms (Horner et al, 2009;Reed, England, Littlejohn, Bass, & Caudillo, 2014;Whittaker et al, 2010), as well as convenience when condoms are not available or sexual encounters are unexpected, and diminished sexual pleasure while using condoms (Daley, 2014;Fennell, 2014;Higgins et al, 2014;Jones et al, 2009;Whittaker et al, 2010). Previous research has also highlighted the important influence of relationship context on the decision to use withdrawal (Brown et al, 2011;Whittaker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies involving small, nonrepresentative samples suggest that perceived subfecundity is associated with reduced odds of contraceptive use and that a nontrivial proportion of women cite fecundity‐related beliefs as reasons for not using contraceptives: For example, they may doubt their ability to become pregnant if they have had unprotected sex and not subsequently conceived . One important exception to this small literature comes from Polis and Zabin .…”
mentioning
confidence: 99%
“…Little is known about community college students’ knowledge and attitudes about their pregnancy risk and contraception, particularly if they identify as gay or bisexual, or have other sexual orientations . However, a 2014 study found that female community college students who did not get pregnant after unprotected intercourse subsequently perceived that their pregnancy risk was low or that they were infertile, and used contraceptives inconsistently . While research on these students’ fertility preferences remains limited, a 2018 survey in Texas suggests an unmet need for both short‐acting hormonal contraceptives and long‐acting reversible contraceptive (LARC) methods …”
mentioning
confidence: 99%
“…2014 study found that female community college students who did not get pregnant after unprotected intercourse subsequently perceived that their pregnancy risk was low or that they were infertile, and used contraceptives inconsistently. 9 While research on these students' fertility preferences remains limited, a 2018 survey in Texas suggests an unmet need for both short-acting hormonal contraceptives and long-acting reversible contraceptive (LARC) methods. 10 Community college students are often subsumed into broader categories of young adults aged 18-25, people of color and low-income populations, the demographic groups associated with the highest rates of unintended pregnancy.…”
mentioning
confidence: 99%